Impact of a transition program with navigator on loss to follow‐up, medication adherence, and appointment attendance in hemoglobinopathies. Issue 8 (2nd May 2019) - Allemang, Brooke; Allan, Kate; Johnson, Colleen; Cheong, Melina; Cheung, Patrina; Odame, Isaac; Ward, Richard; Williams, Suzan; Mukerji, Geetha; Kuo, Kevin H.M.
Abstract: Background: Transition from pediatric to adult care is a period of high risk for loss to follow‐up, morbidity, and mortality in adolescents and young adults (AYA) with hemoglobinopathies. The purpose of this study was to determine whether a transition program with transition navigator (TN) reduced loss to follow‐up and hospitalizations and improved medication adherence and appointment attendance compared with an unstructured transfer. Procedure: A retrospective observational study compared all AYA with hemoglobinopathies who turned 18 one year prior to ( n = 51) and one year after ( n = 61) the initiation of the transition program. Data from one year prior to last pediatric appointment and one year following first adult appointment were collected from each patient. Results: The transition program with TN reduced loss to follow‐up from 29% to 7% ( P = 0.034). A greater proportion of patients in the transition cohort maintained or improved adherence to hydroxyurea or iron chelation to ≥4 days/week; exposure to the program was independently associated with such improvement ( P = 0.047). A trend toward improvement or maintenance of ≥90% attendance to appointments was observed ( P = 0.096). Frequency of hospitalization was not significantly different between the two cohorts ( P = 0.985). Conclusions: A transition program with TN significantly reduced loss to follow‐up, and significantly improved and maintained fair to good medication adherence. Further analysis of economic benefit and patient satisfaction will be conducted.